Pergulatan Diri Aktual Sebagai Pemaknaan Visual Pada Ilustrasi Efek Psikologis Body-Shaming - Nicodemus Koli; Rustono Farady Marta; Natasha Richie Vallerie (Avant Garde, 2021)
The research aims to interpret how media communication are capable of representing body-shaming impacts their victims through the use of illustration. The “efek-psikologis-body-shaming” illustrates how self conflict the victim suffered from body-shaming. Criticizing other’s physique or body-shaming is a part of social interaction. During this process, Individual’s are experiencing physical and psychological anxiety. This anxiety keeps growing as the victim takes more negative commentary from the public. During this dillema, there are two different approaches to adjust one’s physique to the public, whether they accept and cope with it or they simply turn anxious towards any stigma, such as mockery or criticism towards body-shaming. The qualitative research uses interpretive paradigm with the support of semiotics tradition. The study also uses content analysis in order to identify the meaning of the illustration of body-shaming potrayed by “efek-psikologis-body-shaming”. This identification of body-shaming is analyzed through the use of hermeneutic code, such as symbolic, narrative, semantic and cultural. It is discovered in the research that the “efek-psikologis-body-shaming”illustration represents body-shaming’s self conflict. The victim’s self existence and anonymous’ behavior is potrayed deeply within the illustration. Self existence in this context is analyzed through semiotics of visual communication which focuses on verbal and visual meaning.